Seroprevalence of hepatitis B, hepatitis C, and HIV in pregnant women from Eastern Turkey - Esra Çınar Tanrıverdi; Zülal Özkurt; Berrin Göktuğ Kadıoğlu; Handan Alay; Okşan Çalıkoğlu; Özlem Koca; Zeynep Kamalak (Turkish Journal of Gastroenterology, 2019)
Background/Aims: The vertical transmission of hepatitis B virus, hepatitis C virus (HCV), and human immunodeficiency virus (HIV) infections are essential public health problems. In this study, we aimed to investigate the seroprevalence of the aforementioned infections among pregnant women. Materials and Methods: This study was done retrospectively on pregnant women who presented for antenatal follow-up and delivery between 2013 and 2016. Data were collected from the hospital’s electronic health records and patient files. Blood samples were analyzed at the microbiology laboratory of the hospital. HBsAg, anti-HBs, anti-HCV, and anti-HIV titers were tested using the chemiluminescence enzyme immunoassay method (Architect, Abbott Laboratories, USA). Results: HBsAg and anti-HBs levels were tested in 35,295 pregnant women aged 18-45 years. The HBsAg and anti-HBs levels were positive in 425 (1.2%) and 9583 (27.7%) patients, respectively. From 2013 to 2016, the HBV carrier rates have continuously decreased from 1.4% to 0.8%, whereas the anti-HBs positivity has increased from 25.4% to 30.2%. Anti-HCV was detected in 6 of the 9709 (0.06%) patients. All the 7113 pregnant women screened for HIV showed negative results. Conclusion: Hepatitis B carrier rates among pregnant women gradually decreased with a simultaneous increase in the immunity rates. HCV seroprevalence was low and HIV positivity was not encountered in the study population. Cite this article as: Çınar Tanrıverdi E, Özkurt Z, Göktuğ Kadıoğlu B, et al. Seroprevalence of hepatitis B, hepatitis C, and HIV in pregnant women from Eastern Turkey. Turk J Gastroenterol 2019; 30(3): 260-5.